Analysis of needs for development of earthquake disaster mitigation animation videos for disabilities elementary school children - Adik Ismail; Ika Candra Sayekti; Siti Azizah Susilawati; Dias Aziz Pramudita (Jurnal Inovasi Teknologi Pendidikan, 2023)
Earthquakes are frequent disasters in Indonesia. This disaster often causes many fatalities, so reducing the risk of an earthquake is necessary. Disaster risk reduction can be carried out with government programs, namely disaster risk reduction education which aims to reduce the threat of victims due to disasters. However, in implementing this program, there are deficiencies in media accessibility and learning media for elementary school children with disabilities. The purpose of this study was to describe the results of the needs analysis for the development of earthquake disaster mitigation animation videos. This research is a type of qualitative research. The data from this study were obtained from filling out a needs analysis questionnaire by 161 students and 121 teachers from 13 special schools in Klaten Regency, data analysis using interactive analysis. Based on the results of filling out the questionnaire to analyze the needs of students and teachers, it is known that students and teachers of SLB throughout Klaten Regency need an animated video on earthquake disaster mitigation to become one of the learning media. Students agree as much as 97.70%, and teachers agree as much as 99.20% to develop an animated earthquake disaster mitigation video. The development of earthquake disaster mitigation animation videos must follow the needs of students and teachers regarding material, language, presentation, and graphics.